2014
DOI: 10.4238/2014.january.28.9
|View full text |Cite
|
Sign up to set email alerts
|

Association among XRCC1, XRCC3, and BLHX gene polymorphisms and chromosome instability in lymphocytes from patients with endometriosis and ovarian cancer

Abstract: ABSTRACT. Endometriosis is a complex disease that has both benign and malignant characteristics. It affects 5-10% of women of reproductive age. Studies have demonstrated the existence of common genetic changes in endometriosis and ovarian cancer, suggesting a possible association between these 2 diseases. However, the mechanisms that lead to the development of cancer from endometriosis remain unknown. In this study, we evaluated 3 groups of women: 72 patients with endometriosis, 70 with ovarian cancer, and 70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Of the 24 studies related to rs25487, 16 focused on cervical cancer [14–29], 5 on endometrial cancer [30–34], and 3 on ovarian cancer [3537]. The ethnic group was Asian in 11 studies and Non-Asian in the others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 24 studies related to rs25487, 16 focused on cervical cancer [14–29], 5 on endometrial cancer [30–34], and 3 on ovarian cancer [3537]. The ethnic group was Asian in 11 studies and Non-Asian in the others.…”
Section: Resultsmentioning
confidence: 99%
“…The ethnic group was Asian in 11 studies and Non-Asian in the others. Of the 15 studies related to rs1799782, 10 focused on cervical cancer [16–20, 25, 27, 28], 3 on endometrial cancer [35, 37, 38], and 2 on ovarian cancer [30, 31]. The ethnic group was Asian in 7 studies and Non-Asian in 8 studies.…”
Section: Resultsmentioning
confidence: 99%
“…ERCC2 is involved in DNA repair, specifically in nucleotide excision repair. It functions in various types of DNA lesions [12]. Both XRCC2 and ERCC2 are identified as DNA repair genes.…”
Section: Discussionmentioning
confidence: 99%
“…1 4 XRCC genes are involved in base excision repair (BER) and single-strand break in damaged DNA in human genome. 1 5 Molecular epidemiological studies have shown that XRCC genes are significantly associated with lung cancer, 6 9 oral cancer, 10 bladder cancer, 11 13 ovarian cancer, 14 , 15 esophageal cancer, 16 and gastric cancer. 17 23 Moreover, studies have revealed that XRCC gene polymorphism is highly variable in different ethnic populations.…”
Section: Introductionmentioning
confidence: 99%